Knowledge, attitude and practice of contraception among paramedical staff at tertiary care centre - Lamba, Indira; Bhardwaj, Manish Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: To assess the knowledge, attitude and practice of contraception among female paramedical staff, who is already working in the tertiary care hospital and identify the factors that hinders the use of contraception. Methods: This cross-sectional study was done in the Dept. of obstetrics and gynecology, SMS Medical College and attached group of hospitals, Jaipur. The study group included 90 paramedical female staff of reproductive age group (20-45 years) working in this hospital. Their knowledge, attitude and practice on contraceptives were evaluated with the help of a predesigned questionnaire. Results: It was found that 93% of female paramedical staff were using contraceptive method, most of them (70%) using condom (barrier method) as contraceptive. since they were health worker about 88% has Contraceptive Information and 63% also has knowledge about post-partum lactational amenorrhea. 58 % using contraceptive to Preventing unwanted pregnancy. 39% staff discontinued methods due to abnormal uterine bleeding and 20% not adopted any method due to fear of its side effect. Conclusions: Although the level of knowledge, attitude and acceptance of contraception among female paramedical staff were very good but every health worker should teach the community on family planning holistically to increase the awareness so that family planning utilization will be enhanced. This study highlights that knowledge and awareness doesn’t always lead to the use of contraceptives. There is still a need to educate and motivate.